PERAN GURU DALAM MEMANFAATKAN PERPUSTAKAAN UNTUK MENANAMKAN MINAT MEMBACA SISWA KELAS III - St. Erfi Yulvira; BACA SISWA KELAS III St. Erfi Yulvira1 , Indhira Asih Vivi; Rina Yuliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to describe the teachers’ role in utilizing a library to instill the third-grade students’ reading interest. The method used in this study was a descriptive qualitative method. The data were collected through interviews, direct observation, and documentation. This study revealed that the teachers played a role in utilizing a library to instill students’ reading interest. The teachers understood the benefits of a library. In conclusion, the teachers positively impacted students to become more active during learning, and students had a habit of reading activities before learning began.